Nekatera aktualna vprašanja kazenskopravnega varstva pravic iz delovnega razmerja - Kovačič Mlinar, Blaž (Delavci in delodajalci, 2011)
The paper deals with the issue of crimes against labor and social security, particularly in terms of innovations introduced by the new Penal Code of 2008 (PC-1). In addition, it also presents problems of non-payment of social security contributions in more detail. It is an offense that was included in the previous Penal Code (PC), but lately there have been some significant changes in the interpretation of the statutory character of this crime in practice.
Keywords: delovno pravo; kazensko pravo; kazniva dejanja; kršenje; mobing; neplačevanje prispevkov; pravice; socialna varnost; zaposleni